Mengkaji Hubungan Kausalitas Antara Konsumsi Energi Terbarukan Dan Pertumbuhan Ekonomi: Studi Kasus China - Ardi, Nisful; Yuliawan, Dedy (Shofanah Media Berkah, 2025)
This study aims to analyze the causal relationship between renewable energy consumption and economic growth in China over the period 1990 to 2023. Utilizing the Vector Error Correction Model (VECM) and Granger causality tests, the research explores both short-run and long-run dynamics between the two variables. The stationarity test results indicate that the data are non-stationary at level but become stationary after first differencing. The Johansen cointegration test confirms a long-term relationship between the variables. The VECM and Granger causality test results reveal a unidirectional causal relationship running from renewable energy consumption to economic growth. The Impulse Response Function (IRF) shows that shocks from renewable energy consumption initially have a negative impact on economic growth, but this effect turns positive in the long run. Meanwhile, the Variance Decomposition analysis indicates that the contribution of renewable energy to economic growth increases over time. These findings highlight the crucial role of renewable energy development in supporting long-term sustainable economic growth and offer important implications for developing countries undergoing energy transitions.